Análisis de la normativa ambiental local para el mejor manejo de plásticos en el cantón Guaranda año 2021. - Rivera Yépez, Patricio Fernando (2023)
This proposed research work has its origin in the need to apply environmental regulations in each locality to protect the environment and beside it the well-being and the population health. The environmental damage is evident and therefore since December 21, 2020, the "Organic Law for the Rationalization, Reuse and Reduction of Single-Use Plastics" has been in force; whose purpose is the regulation and progressive reduction of the use of plastics; establishing clear policies of responsible consumption, regulation of the generation of plastic waste and recycling of products in order to protect the environment and thereby contribute to a healthy environment for the population. The research focuses on Canton Guaranda as one of the smallest central cities in the country and the applicability of the regulations described at the local level in order to analyze and investigate the existence of local ordinances and protocols that allow supporting due compliance with the National Organic Law enunciated above, by virtue of the fact that this is a contribution that strengthens the control and social compliance of both natural and legal persons to curb environmental damage and promote social awareness by generating a culture of environmental protection. The methodology to be used Quantitative is associated with the positivist tradition, which conceives social reality as an objective structure. The facts or social phenomena studied in this work are measurable and quantifiable. I will measure and establish causal relationships between the variables, to explain the study problem and the current social reality. The methodology to be used is quantitative and is associated with the positivist tradition, which conceives social reality as an objective structure. The facts or 3 social issues studied in this work are measurable and quantifiable. I will measure and establish causal relationships between the variables, to explain the study problem and the current social reality.